Aplikasi Kamus Bahasa Daerah Serawai Menggunakan Algoritma Bubble Sort dan Voice Recognition Berbasis Android - Juhardi, Ujang; Sahputra, Eka (UNIVED Press, 2018)
In general, native Sumatran people speak their mother tongue (B1) of the Malay language family. Each region in Sumatra generally has a different regional language. Specifically in Bengkulu, there are nine regional languages, namely Serawai language, Pekal language, Rejang language, Pasemah language, Mulak language, Kaur Bintuhan language, Bengkulu Malay language, Enggano language, and Muko-muko language. In the beginning, to search for a translation of the Serawai language, no one had ever used conventional dictionary facilities and internet online dictionary directories. So it is necessary to innovate in developing a Serawai language dictionary application to make searching easier, accompanied by database update content facilities and voice recognition. Therefore, it is hoped that by making this application it can become a useful medium and suit what users need. So the problem was formulated on how to create a Serawai Regional Language Dictionary using the Android-based Bubble Sort and Voice Recognition algorithm. In the data collection method, observation and literature study were used. The benefit of this research is to make it easier for the local government of South Bengkulu Regency to introduce the Serawai regional language to the wider community by utilizing Android-based information technology.